STRUCTURAL AND FUNCTIONAL MODEL OF INVOLVING PRESCHOOL CHILDREN TO HOCKEY ACTIVITIES - Istomin, S.O.; Naboychenko, E.S.; Kachalov, D.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the effectiveness of the implementation of the structural-functional model of introducing children aged 5-7 years to hockey. Methods and structure of the study. Conducted pedagogical experiment, quantitative and qualitative analysis; methods of mathematical statistics. The contingent of the study is children aged 5-7 years (n=120) who have been studying at the Sports school of the Olympic Reserve "Spartakovets" for three years (2014-2016). Results and conclusions. Groups of children in which the structural-functional model of introducing children aged 5-7 years to hockey lessons was implemented have a high level of involvement in sports activities according to the criteria: motivational, emotional-volitional, evaluative-behavioral, physical readiness. The presented results can be used in the implementation of sports and recreation programs with elements of the chosen sport.